2006
DOI: 10.1016/j.cub.2006.01.050
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Map of Conserved MicroRNA Targets in C. elegans

Abstract: At least 10% of C. elegans genes are predicted miRNA targets, and a number of nematode miRNAs seem to regulate biological processes by targeting functionally related genes. We have also developed and successfully utilized an in vivo system for testing miRNA target predictions in likely endogenous expression domains. The thousands of genome-wide miRNA target predictions for nematodes, humans, and flies are available from the PicTar website and are linked to an accessible graphical network-browsing tool allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
316
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(322 citation statements)
references
References 63 publications
5
316
0
1
Order By: Relevance
“…We observed overall similar results with this method but found that many seeds did not generate sizable control seeds that satisfied the tolerance for frequency in the transcriptome. We therefore preferred the former strategy, which has been used in several target studies in various animal clades Krek et al 2005;Lall et al 2006).…”
Section: Analysis Of Conserved Target Propertiesmentioning
confidence: 99%
“…We observed overall similar results with this method but found that many seeds did not generate sizable control seeds that satisfied the tolerance for frequency in the transcriptome. We therefore preferred the former strategy, which has been used in several target studies in various animal clades Krek et al 2005;Lall et al 2006).…”
Section: Analysis Of Conserved Target Propertiesmentioning
confidence: 99%
“…Using the algorithms for target gene prediction, including PicTar (Lall et al, 2006), TargetScan (Lewis et al, 2003), and miRanda (John et al, 2004), the key enzyme in DNA methylation, DNMT3A, was identified as one of the potential targets of miR-143. The predicted binding of miR-143 with DNMT3A 3 0 UTR is illustrated in Figure 2A.…”
Section: In Silico Prediction Of Mir-143 Targetmentioning
confidence: 99%
“…Another function of the 3 0 region of a miRNA is to give specificity to the members of miRNA families that share identical seeds but they diverge in their 3 0 sequences (Brennecke et al, 2005). The recognition of the principles of miRNA targeting accelerated the development and improvement of a series of bio-computational approaches to predict miRNA targets in animals that produced a remarkably large number of putative miRNA-regulated transcripts further emphasizing the significance of miRNAs (Enright et al, 2003;Stark et al, 2003;Kiriakidou et al, 2004;Lewis et al, 2005;Lall et al, 2006).…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 99%